The Role of Local Governments in the Development of Amateur Sports (Erzurum Metropolitan Municipality Example) - Necip Fazıl Kıshali; Vahdet Alaeddinoğlu; Ahmet Dal (ümit doğan üstün, 2021)
Success in sports infrastructure depends on the establishment of a sustainable system by giving importance to children with human resources and their upbringing. In order to establish such system, the trainer, facility, athlete resource and their management should be carried out with good planning and project planning. The support given by local governments to sports infrastructure is of great importance in the development of sports infrastructure. The aim of this research was to examine the sports policy of Erzurum Metropolitan Municipality for the development of sports infrastructure. In the research, document scanning method was used based on content analysis. In order to evaluate the results of the research comparatively, the annual activity reports of 8 metropolitan municipalities between 2015-19 published in their websites, were investigated mutually. The population ratios of the chosen cities are close to each other. The sports facility investments of the municipalities were evaluated in terms of the number of licensed athletes, number of summer and winter sports schools, number of club branches, the number of trainers, and national and international sports organizations. The data were evaluated with SPSS for Windows 22 using Chi Square analyses. As a result, it was found that among other metropolitan municipalities, Erzurum metropolitan municipality was found to be in the first place in the number of summer and winter sports schools, number of club branches, and national and realized international sports organizations.